2005
DOI: 10.1002/pmic.200401318
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of mouse liver plasma membrane: Use of differential extraction to enrich hydrophobic membrane proteins

Abstract: To comprehensively identify proteins of liver plasma membrane (PM), we isolated PMs from mouse liver by sucrose density gradient centrifugation. An optimized extraction method for whole PM proteins and several methods of differential extraction expected to enrich hydrophobic membrane proteins were tested. The extracted PM proteins were separated by 2-DE, and were identified by MALDI-TOF-MS, and ESI-quadrupole-TOF MS. As the complementary method, 1-DE-MS/MS was also used to identify PM proteins. The optimized l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 35 publications
8
82
0
4
Order By: Relevance
“…3B). Similar results have been reported in 2-DGE-based studies of other organisms, even though those studies contained technical differences like extraction of membrane proteins with Triton X-114 to enrich membrane proteins (Klein et al, 2005;Zhang et al, 2005;Mattow et al, 2007). For example, the very recent 2-DGE analysis of the plasma membrane proteome of mycobacteria identified a maximal number of three TMDs in a protein (Mattow et al, 2007).…”
Section: Sec-mudpit Approach Identifies a 3-fold Higher Number Of Memsupporting
confidence: 67%
“…3B). Similar results have been reported in 2-DGE-based studies of other organisms, even though those studies contained technical differences like extraction of membrane proteins with Triton X-114 to enrich membrane proteins (Klein et al, 2005;Zhang et al, 2005;Mattow et al, 2007). For example, the very recent 2-DGE analysis of the plasma membrane proteome of mycobacteria identified a maximal number of three TMDs in a protein (Mattow et al, 2007).…”
Section: Sec-mudpit Approach Identifies a 3-fold Higher Number Of Memsupporting
confidence: 67%
“…yeast membrane proteins with a grand average of hydropathy (GRAVY) value ,0.4 [9], which falls into the solubility range commonly detected on 2D gels. Our previous study [30] also showed that PM proteins can be better separated by 2-DE through an optimized extraction method. So in this work, 2-DE methodology was used to analyze the liver PM proteome, and 13 protein spots with a greater than 2-fold difference were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane proteins were extracted with 2% Triton X-114 detergent for temperature-dependent phase separation and precipitated by ice-cold acetone (37). Samples from different culture conditions were analyzed by SDS-polyacrylamide gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%